2023
DOI: 10.1186/s12964-023-01089-1
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona and exosomes: new challenges and prospects

Abstract: Recent advances in extracellular vesicle (EVs) detection and isolation methods have led to the development of novel therapeutic modalities. Among different types of EVs, exosomes (Exos) can transfer different signaling biomolecules and exhibit several superior features compared to whole-cell-based therapies. Therapeutic factors are normally loaded into the Exo lumen or attached to their surface for improving the on-target delivery rate and regenerative outcomes. Despite these advantages, there are several limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 131 publications
0
22
0
Order By: Relevance
“…The protein corona is a set of proteins and other molecules adsorbed to the EVs. These proteins can be bioactive and mediate part of the immunomodulatory potential ( 16 , 17 ). All of this heterogeneity of methods brings at the same time strength to the immunomodulatory response of EVs as a global effect, but brings hardship as to determine what is driving this specific effect.…”
Section: Multiparametric Influence On the Immunomodulatory Potential ...mentioning
confidence: 99%
“…The protein corona is a set of proteins and other molecules adsorbed to the EVs. These proteins can be bioactive and mediate part of the immunomodulatory potential ( 16 , 17 ). All of this heterogeneity of methods brings at the same time strength to the immunomodulatory response of EVs as a global effect, but brings hardship as to determine what is driving this specific effect.…”
Section: Multiparametric Influence On the Immunomodulatory Potential ...mentioning
confidence: 99%
“…In general, the NTA analyses (NTA control representative images are reported in Figure S1) showed that EVs samples prepared with the addition of biological-derived excipients had a higher compositional and dimensional complexity, due to the presence of nanostructures in many cases close to or below the resolution limit of the investigation technique comprising biomolecules, supramolecular complexes, extracellular matrix components, and nonvesicular cellular origin nanoparticles such as exomeres and supermeres that can be isolated only with ultracentrifugations ranging from 150 000 to almost 400 000 g . In detail, upon lyophilization, EVs with biological-derived excipients had higher concentrations, due to the presence of nanostructures and nanoparticles not discarded from the excipients and dimensions, due to the protein corona formation around the EVs. , …”
Section: Resultsmentioning
confidence: 99%
“…Most likely, reconstituting EVs for the in vitro tests with lymphocytes’ culture medium, the establishment of a protein corona around EVs rich in substances attractive to lymphocytes was favored. Many authors have already illustrated how a protein corona is naturally shaped around the surface of EVs , in biological fluids, affecting vesicle diameter as well mobility . In addition, EVs freeze-dried with the presence of biologically derived fluid demonstrated a significantly higher internalization by both cell lines compared to the other samples.…”
Section: Discussionmentioning
confidence: 99%
“…While the highest purity is desired for intravenous infusion, the requirement for other routes of administration such as topical application or subcutaneous injection could be less stringent. Moreover, substantial removal of protein and nucleic acid contaminants could impact certain physicochemical properties of sEVs such as tendency to aggregate and plastic adsorption; as well as composition of the protein corona that ultimately influences in vivo biodistribution and cellular uptake efficiency (Görgens et al, 2022;Heidarzadeh et al, 2023). Whether these aspects are negatively affected and the solutions to improve them have to be addressed in future studies.…”
Section: Parametersmentioning
confidence: 99%